2017
DOI: 10.5152/ucd.2017.3329
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of fine needle aspiration biopsy in large thyroid nodules

Abstract: Objective: Fine needle aspiration biopsy provides one of the most important data that determines the treatment algorithm of thyroid nodules. Nevertheless, the reliability of fine needle aspiration biopsy is controversial in large nodules. The aim of this study was to evaluate the adequacy of fine needle aspiration biopsy in thyroid nodules that are four cm or greater. Material and Methods:We retrospectively examined 219 patients files who underwent thyroidectomy for thyroid nodules that were greater than four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…A meta-analysis of 35 studies and 12,834 autopsies between 1949 and 2007 found ITC up to 11.2%.The interesting finding in this study is that there is no significant increase in prevalence in autopsy studies since the 1940s.This finding strongly supports the link between development of diagnostic methods and increase in the incidence of ITC in the present day [12]. In the diagnosis and follow-up of thyroid nodules clinically and radiologically as recommended in the American Thyroid Association (ATA) guidelines; Ultrasound guided FNAC because of its low cost and easy and simple method and Bethesda Scoring System for interpretation is widely preferred all over the world [13][14][15]. When the studies in the literature are examined, hyperthyroidism and benign MNG are the most common indications for patients operated with benign causes.…”
Section: Discussionsupporting
confidence: 72%
“…A meta-analysis of 35 studies and 12,834 autopsies between 1949 and 2007 found ITC up to 11.2%.The interesting finding in this study is that there is no significant increase in prevalence in autopsy studies since the 1940s.This finding strongly supports the link between development of diagnostic methods and increase in the incidence of ITC in the present day [12]. In the diagnosis and follow-up of thyroid nodules clinically and radiologically as recommended in the American Thyroid Association (ATA) guidelines; Ultrasound guided FNAC because of its low cost and easy and simple method and Bethesda Scoring System for interpretation is widely preferred all over the world [13][14][15]. When the studies in the literature are examined, hyperthyroidism and benign MNG are the most common indications for patients operated with benign causes.…”
Section: Discussionsupporting
confidence: 72%
“…It might be caused most of the cases were taken intraoperatively without ultrasound guidance. Other factors including the inadequate amount of cells for the analysis, fixation method, presence of non-homogenous nodule, and subjectivity of the pathologist who interprets the cytology slides could affect the FNAB results (Bozbiyik et al, 2017). As a consequence, many patients may undergo diagnostic surgery and raising the risk of morbidity if they are ultimately diagnosed as a benign disease.…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 other series have reported on the adenoma rate of operated thyroid nodules ≥4 cm 811 . The overall surgical prevalence of adenoma varied widely at 6.3% 11 , 11% 10 and 28% 9 . The current study had the highest rate of adenoma reported to date, at 30% of operated nodules ≥4-cm.…”
Section: Discussionmentioning
confidence: 99%